Sensory and consumer research in food product design and development - Moskowitz, Howard R.; Beckley, Jacqueline H.; Resurreccion, Anna V. A. (Institute of food technologists series, 2012)
Sensory and Consumer Research in Food Product Design and Development, Second Edition provides both theory and case histories illustrating the types of issues faced by food professionals, the nature of the thinking and the way problems can be solved in a practical format